Stock trading and prediction using weakly supervised learning - Tan, Nigel Jun Wen (Nanyang Technological University, 2021)
This project attempts to use both technical analysis and sentimental analysis to predict stock market prices. The method in this published paper, Deep Learning Approach for Short-Term Stock Trends Prediction Based on Two-Stream Gated Recurrent Unit Network, will be replicated. After which, modifications will be made to try to improve on the results achieved in the published paper. Historical price of the S&P500 will be used along with news article from Bloomberg and Reuters.